The Traveler's Gift: Seven Decisions that Determine Personal Succes - Andy Andrews (Thomas Nelson Publishers, 2002)
"David Ponder is at a crossroads. Having lost his job and the will to live, he has been supernaturally selected to travel through time, gathering wisdom for future generations. Visits to historical figures such as Abraham Lincoln, King Solomon, and Anne Frank yield the Seven Fundamentals for Success that will impact the entire world"--Page 4 of cover.